2017
DOI: 10.1371/journal.pone.0171722
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of heat shock protein 70 genes (HSPA1A, HSPA1B and HSPA1L) and susceptibility of noise-induced hearing loss in a Chinese population: A case-control study

Abstract: Noise-induced hearing loss (NIHL) is the second-most frequent form of sensorineural hearing loss. When exposed to the same noise, some workers develop NIHL while others do not, suggesting that NIHL may be associated with genetic factors. To explore the relationship between single nucleotide polymorphisms (SNPs) in heat shock protein 70 (HSP70) genes (HSPA1A, HSPA1B and HSPA1L) and susceptibility to NIHL in Han Chinese workers exposed to noise, a case-control association study was carried out with 286 hearing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
(35 reference statements)
0
14
0
3
Order By: Relevance
“…An increased expression of HSP70 has been found in cochlea cells under noise exposure and they further act as a protective factor in the development of NIHL [ 12 ]. What is noteworthy is that some studies indicated a close association between several SNPs in HSP70 genes, including rs1043618 [ 13 , 14 ], rs2763979 [ 15 ], rs2227956 [ 14 , 15 ], and rs1061581 [ 14 ] (the characteristics of these SNPs are listed in Table 1 ), and NIHL susceptibility, whereas no positive result for rs1043618, rs2227956 and rs1061581 was found in Yang‘s study [ 16 ]. For each SNP site, the conclusion in different studies is also diverse.…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression of HSP70 has been found in cochlea cells under noise exposure and they further act as a protective factor in the development of NIHL [ 12 ]. What is noteworthy is that some studies indicated a close association between several SNPs in HSP70 genes, including rs1043618 [ 13 , 14 ], rs2763979 [ 15 ], rs2227956 [ 14 , 15 ], and rs1061581 [ 14 ] (the characteristics of these SNPs are listed in Table 1 ), and NIHL susceptibility, whereas no positive result for rs1043618, rs2227956 and rs1061581 was found in Yang‘s study [ 16 ]. For each SNP site, the conclusion in different studies is also diverse.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional method for the early diagnosis of noise-induced hearing loss is Cys/Cys genotype, and the sensitivity of the rs2763979 locus [14] [15]. The results of twin studies showed that monozygotic pairs were more similar with regards to noise sensitivity than dizygotic pairs, and quantitative genetic modeling indicated significant familiality.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown the association of susceptibility genes, such as catalase (CAT), heat shock protein70 (HSP70), cadherin-23 (CDH23), caspase (CASP), and NADPH oxidase3 (NOX3), with the development of NIHL [12][13][14][15][16][17][18]. Additionally, previous studies have demonstrated that smoking, stressful lifestyle, and physical exercise are associated with hearing loss [19][20][21].…”
Section: Introductionmentioning
confidence: 99%